Strategies of Islamic Education Teachers in Motivating Students to Memorize the Qur’an through the Tahfidz Quarantine Program at Islamic Boarding School - Rani Selviani; Sutarto Sutarto; Jumira Warlizasusi (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2025)
ENGLISH: Strategies of Islamic Education Teachers in Motivating Students to Memorize the Qur’an through the Tahfidz Quarantine Program at Boarding SchoolObjective: This study aims to identify the strategies implemented by teachers to motivate students to memorise the Quran in the Tahfidz Quarantine Program at the Cahaya Qur'an Tahfidz Islamic Boarding School. Method: This study employs a descriptive qualitative approach. Data was collected through interviews with the foundation chairman, teachers, and students involved in the Quran Memorisation Quarantine Program. Results: Students' motivation to memorise the Quran includes intrinsic and extrinsic factors. Teachers employ review sessions, emotional support, relevance of memorisation to daily life, and regular nightly evaluations to address declining motivation. Conclusion: The teachers' motivational strategies at the Cahaya Qur'an Tahfidz Boarding School, such as murojaah, emotional attention, relevance of memorisation to life, and routine evaluation, are effective in maintaining students' enthusiasm, achieving memorisation targets, and balancing intrinsic and extrinsic motivation. Contribution: This study contributes to developing teaching strategies for tahfidz programs in boarding schools, serving as a reference for educators and administrators in designing more effective programs to motivate students to memorise the Qur'an.INDONESIAN: Strategi Guru PAI dalam Memotivasi Santri Menghafal Al-Qur’an melalui Program Karantina Tahfidz di PesantrenTujuan: Penelitian ini bertujuan untuk mengetahui strategi yang diterapkan oleh guru dalam memotivasi santri untuk menghafal Al-Qur'an pada Program Karantina Tahfidz di Pesantren Tahfidz Cahaya Qur'an. Metode: Penelitian ini menggunakan pendekatan kualitatif deskriptif. Data diperoleh melalui wawancara dengan ketua yayasan, guru, dan santri yang terlibat dalam program Karantina Tahfidz. Hasil: Motivasi santri dalam menghafal Al-Qur'an meliputi intrinsik dan ekstrinsik. Untuk mengatasi penurunan motivasi, guru menggunakan strategi murojaah, perhatian emosional, relevansi hafalan dengan kehidupan, dan evaluasi rutin setiap malam. Kesimpulan: Strategi motivasi guru di Pesantren Tahfidz Cahaya Qur'an, seperti murojaah, perhatian emosional, relevansi hafalan dengan kehidupan, dan evaluasi rutin, efektif dalam menjaga semangat santri, mencapai target hafalan, serta menyeimbangkan motivasi intrinsik dan ekstrinsik. Kontribusi: Penelitian ini memberikan kontribusi bagi pengembangan strategi pengajaran program tahfidz di pesantren, sebagai referensi bagi pendidik dan pengelola dalam merancang program yang lebih efektif untuk memotivasi santri menghafal Al-Qur'an.